Ethylene and auxin: new insights into the hormonal regulation of tomato fruit ripening - Gomes, Bruna Lima (2017)
Our knowledge of the factors mediating ethylene-dependent and -independent ripening of climacteric fruit remains limited. Besides the known importance of ethylene roles, auxin has also been emerged as crucial to regulating ripening. Furthermore, the crosstalk between ethylene and auxin in tomato fruit ripening still awaits clarification. ERFs (Ethylene Responsive Factors) are transcription factors belonging to a large family acting downstream on ethylene signaling that direclty regulate ripening-related metabolisms, but their specific roles are still lacking. We present here a comprehensive expression profiling of tomato ERFs in wild-type and tomato ripening-impaired tomato mutants (Nr, rin and nor) indicating that out of the 77 ERFs present in the tomato genome, 27 show enhanced expression at the onset of ripening, while 28 display a ripening-associated decrease in expression, suggesting that different ERFs may have contrasting roles in fruit ripening. Members of subclass E, ERF.E1, ERF.E2 and ERF.E4, show dramatic down-regulation in the ripening mutants suggesting their expression might be instrumental to fruit ripening. The study illustrates the high complexity of the regulatory network interconnecting RIN and ERFs and identifies subclass E members as the most active ERFs in ethylene- and RIN/NOR-dependent ripening. Additionally, with the aim to shed more light into ethylene and auxin interplay, hormonal treatments were applied to tomato fruits and several ripening aspects were then evaluated such as the volatile profile. Overall, results elicited that auxin delay the onset of ripening further showing epistatic effects over the influence of ethylene. Several ripening-related genes, including components of the ethylene signaling, were affected by auxin suggesting potential crosstalk points between the two hormones. Moreover, ethylene appears as potentially part of the auxin regulation through inducing its conjugation. The modulation of hormone levels in tomato fruit throughout ripening can be useful to help designing approaches that both improve fruit quality and extend shelf life.